Peran Layanan Perencanaan Individual dalam Membantu Self-Adjustment Siswa Generasi Z di Lingkungan Sekolah (International Forum of Researchers and Lecturers, 2025)
Generation Z, growing up in the digital era, faces various challenges in social, emotional, and academic adjustment in the school environment. This study aims to determine the effectiveness of individual planning services in improving the adjustment abilities of Generation Z students. A qualitative approach was used with a literature review from the past five years. The results of the study indicate that the use of digital technology to support students' personal development can help them better understand themselves, set goals, and plan adaptive steps. This service also plays a role in providing support and early intervention, which helps counselors shift from a reactive approach to a more proactive one. The findings of this study underscore the importance of changing the role of counselors, from being responsive to being more proactive and preventative, by integrating personal and technological approaches in the mentoring process. Therefore, guidance and counseling teachers are advised to design services that are more structured, participatory, and relevant to the unique characteristics of Generation Z. This will ensure that the services provided are more effective in helping students adjust to the school environment.